2014
DOI: 10.1093/toxsci/kfu098
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Lung Damage Caused by a Nanofilm Spray Product

Abstract: Inhalation of waterproofing spray products has on several occasions caused lung damage, which in some cases was fatal. The present study aims to elucidate the mechanism of action of a nanofilm spray product, which has been shown to possess unusual toxic effects, including an extremely steep concentration-effect curve. The nanofilm product is intended for application on non-absorbing flooring materials and contains perfluorosiloxane as the active film-forming component. The toxicological effects and their under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…The observed effects were comparable to those found in live rats and indicated that the spray products damaged the surfactant film. We have shown inhibition of pulmonary surfactants using the Langmuir technique (Duch et al, 2014;Larsen et al, 2014) and the interactions have been demonstrated using porcine (HL-10 (Vermehren et al, 2006) and Curosurf ® (Bernhard et al, 2000)) as well as bovine (Alveofact ® (Gunther et al, 2002)) pulmonary surfactant formulations. Results from these relatively diverse pulmonary surfactant formulations were in overall agreement, suggesting that pulmonary surfactant inhibition is a robust and reliable endpoint.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The observed effects were comparable to those found in live rats and indicated that the spray products damaged the surfactant film. We have shown inhibition of pulmonary surfactants using the Langmuir technique (Duch et al, 2014;Larsen et al, 2014) and the interactions have been demonstrated using porcine (HL-10 (Vermehren et al, 2006) and Curosurf ® (Bernhard et al, 2000)) as well as bovine (Alveofact ® (Gunther et al, 2002)) pulmonary surfactant formulations. Results from these relatively diverse pulmonary surfactant formulations were in overall agreement, suggesting that pulmonary surfactant inhibition is a robust and reliable endpoint.…”
Section: Discussionmentioning
confidence: 95%
“…The method has recently been used to test the toxic effect of a specific nanofilm impregnation product and the effect of the solvent on the product toxicity . In addition, a strong correlation was observed between the CS and the Langmuir balance (Larsen et al, 2014). The Langmuir balance measures the surface pressure of spread films on a liquid subphase.…”
Section: Research Articlementioning
confidence: 90%
“…In our study, patients with WAP had alveolitis and/or alveolar hemorrhage on histopathological examination, and macrophages constituted the dominant cell type in the BALF. In a past report, the mechanism underlying WAP, namely, the inhalation of fluororesin in a waterproof spray, induces macrophage infiltration and thickening of the alveolar septum, increased airway resistance, and reduced expiratory flow rate in mice [45,46]. These mechanisms might induce the macrophage domination in the BALF findings of patients with WAP.…”
Section: Discussionmentioning
confidence: 98%
“…The fast and irreversible response resembles the effects previously observed after exposing mice to impregnation spray products, 33 for which the mechanism of toxicity was shown to be the inhibition of LS function. 15,16,18 However, the acute effects of ZnO NP inhalation may also be triggered by other mechanisms in the lungs, such as stimulation of nerves, disruption of barrier function, and triggering inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of LS function has been linked to acute inhalation toxicity, for example, for impregnation products where disruption of LS function correlates with an irreversible decrease in tidal volume of the exposed mice. 15 -18…”
Section: Introductionmentioning
confidence: 99%